Neuromuscular blockade with acute respiratory failure in a patient receiving cibenzoline. Issue 6 (June 1997) - Similowski, T; Straus, C; Attali, V; Girard, F; Philippe, F; Deray, G; Thomas, D; Derenne, J P
Abstract : Cibenzoline is a class Ic antiarrhythmic agent that can be used to treat supraventricular arrhythmias. A case is reported of cibenzoline overdose in a patient with impaired renal function, leading not only to the usual cardiac and metabolic symptoms (bradycardia and hypoglycaemia), but also to a myastheniform syndrome with acute respiratory failure. Neuromuscular blockade was demonstrated by repetitive supramaximal stimulation of the median nerve, and diaphragmatic involvement was evidenced by applying the same protocol to the phrenic nerve. Muscle strength recovered as serum cibenzoline levels decreased, allowing the patient to be weaned from the ventilator. This observation suggests that cibenzoline, like other antiarrhythmic agents, can be responsible for neuromuscular blockade, and should therefore be used with caution in patients with neuromuscular and respiratory diseases or with impaired renal function.